IDEAL, the Infectious Diseases of East African Livestock project open access database and biobank - Callaby, R.; Pendarovski, C.; Jennings, A.; Mwangi, S.T.; Wyk, Ilana Conradie van; Mbole-Kariuki, M.; Kiara, Henry K.; Toye, Philip G.; Kemp, Stephen J.; Hanotte, Olivier H.; Coetzer, Jacobus A.W.; Handel, Ian G.; et al. (Springer, 2020)
The Infectious Diseases of East African Livestock (IDEAL) project was a longitudinal cohort study of calf health which was conducted in Western Kenya between 2007–2010. A total of 548 East African shorthorn zebu calves were recruited at birth and followed at least every 5 weeks during the first year of life. Comprehensive clinical and epidemiological data, blood and tissue samples were collected at every visit. These samples were screened for over 100 different pathogens or infectious exposures, using a range of diagnostic methods. This manuscript describes this comprehensive dataset and bio-repository, and how to access it through a single online site (http://data.ctlgh.org/ideal/). This provides extensive filtering and searching capabilities. These data are useful to illustrate outcomes of multiple infections on health, investigate patterns of morbidity and mortality due to parasite infections, and to study genotypic determinants of immunity and disease.